Methodological Basis of the Theoretical and Legal Research of Integration Processes in Modern States - Nikolaevna Klyukovskaya, Irina; Yurievich Cherkashin, Evgeny; Ruslanovich Gabrilyan, Roman; Yegorovich Semenov, Viktor; Kurmanovich Melekayev, Ruslan (International Journal of Engineering and Technology, 2018)
This article specifies theoretical globalization-related problems that require more detailed and scrupulous consideration. The study defines the objectivity of teleological processes, factors affecting their course and forms established under their influence. The authors analyze methodological proofs of global integration processes in the modern world. Using dialectical, historical-legal and comparative-legal research methods, the authors have determined circumstances forming various types of globalization, ways to resolve globalization-caused conflicts through the common-cause factor (optimization through the recognition and declaration of goals and their underlying values) or the institutional system of formal and actual dominants that structures the international hierarchy of states and defines power poles.The scientific novelty of this study consists in the analysis of objective globalization-related problems regardless of propagandist and ideological stereotypes from the viewpoint of scientific pragmatism and formal-logical rules.Â Â